Numerical Simulation of Thrombolysis in Robot-Assisted Retinal Vein Cannulation - Shunlei Li; Jiawen Pan; Juan Ji; Guanghang Wang; Baobao Qi (Complexity)
Robot-assisted retinal cannulation is an eye surgical procedure which can dissolve the obstruction by using robot to inject anticoagulant into occluded vessel. The current research on the critical parameters of cannulation for human is scarce because of the immature technology. Considering the influence of microneedle, this work investigated the effects of drug concentration, injection velocity, injection position, and size of clot on cannulation by theoretical analysis and finite element analysis. For finite element analysis, the multiphysics continuum model was established to demonstrate species transport and reaction which simulates the entire lytic process of the occlusive clot, and four cell zones were established to describe the generation of plasmin (PLS) with the addition of tissue-type plasminogen activator (tPA) and fibrinolysis of clot by importing subroutines into each cell zone under the conditions of constant clot size and variable size, respectively. The results imply that the most efficient value of tPA concentration is 50 nM, injection velocity is 60 mm/s for clot length of 0.1 mm, and the best position to insert the cannula is 0.5 mm in front of the thrombus. For different clot lengths of 0.1 mm to 0.6 mm, the optimal range of tPA concentration and injection velocity is from 20 nM to 70 nM and from 40 mm/s to 60 mm/s, respectively, and explores the reasonable injection position of 0.3 mm to 0.5 mm in front of clot in a vein of 100 μm. This conclusion can be used to perform robot-assisted cannulation surgery to improve fibrinolytic efficiency.